Transition‐Metal‐Free Multicomponent Approach to Stereoenriched Cyclopentyl‐isoxazoles through C−C Bond Cleavage. Issue 16 (27th July 2018) - Subramanian, Parthasarathi; Kaliappan, Krishna P.
Abstract: An efficient multicomponent reaction for the synthesis of stereoenriched cyclopentyl‐isoxazoles from camphor‐derived α‐oximes, alkynes, and MeOH is reported. Our method involved a series of cascade transformations, including the in situ generation of an I III catalyst, which catalyzed the addition of MeOH to a sterically hindered ketone. Oxidation of the oxime, and rearrangement of the α‐hydroxyiminium ion generated a nitrile oxide in situ, which, upon [3+2] cycloaddition reaction with an alkyne, delivered the regioselective product. This reaction was very selective for the syn ‐oxime. This multicomponent approach was also extended to the synthesis of a new glycoconjugate, camphoric ester‐isoxazole C ‐galactoside. Abstract : Many components make light work : A multicomponent reaction for the synthesis of stereoenriched cyclopentyl‐isoxazoles from camphor‐derived α‐oximes, alkynes, and MeOH is reported. Our strategy involves the in situ generation of ArI III, which catalyzes a concomitant methanolysis of the ketone, C−C bond cleavage, and the formation of a nitrile oxide, which in turn serves as a dipole for the alkyne and produces the chirally enriched isoxazole.